Halophytes as Possible Source of Antioxidant Compounds, in a Scenario Based On Threatened Agriculture and Food Crisis - Marius-Nicusor GRIGORE; Lacramioara OPRICA (Tehran University of Medical Sciences, 2015)
Letter to the Editor